The effects of plasma exchange and glucocorticoids on early kidney function among patients with ANCA-associated vasculitis in the PEXIVAS trial - Uchida, Lisa; Pusey, Charles D.; Jayne, David R.W.; Walters, Giles; Jardine, Meg; Perkovic, Vlado; Cass, Alan; Summers, Shaun; Kerr, Peter; Noble, Euan; Johnson, David W.; Peh, Chen Au; et al. (Kidney international, 2025)
Therapeutic plasma exchange (PLEX) is an adjunctive treatment for patients with anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis and kidney involvement. Little is known about the effect of PLEX on early changes in kidney function. This post-hoc analysis of the PEXIVAS trial investigated the effects of PLEX on changes in kidney function within 12 months. PEXIVAS was a randomized controlled trial recruiting 691 patients with ANCA-associated glomerulonephritis, of whom 349 underwent PLEX and 342 received no-PLEX. The primary outcomes of this post hoc study of PEXIVAS were change in estimated glomerular filtration rate (eGFR) from baseline and recovery of kidney function (defined as eGFR increase of 15ml/min/1.73m2 or more). Baseline eGFR was 21.7 ± 20.3 and 20.6 ± 18.7 ml/min/1.73m2 in the PLEX and no-PLEX groups, respectively. Mean improvements in eGFR at weeks two, four, and eight after initiation of therapy were greater for the PLEX vs. the no-PLEX groups. The greatest significant difference in recovery of kidney function in the PLEX compared to the no-PLEX groups was at week four (relative risk (RR): 1.41; 95% confidence interval:1.09-1.82). Increased eGFR or recovery of kidney function at week four were significantly associated with lower risk for end-stage kidney disease at week 52 (RR: 0.96: 0.95-0.97, and RR: 0.29: 0.16-0.52; respectively). Neither changes in eGFR nor recovery of kidney function differed by reduced- compared to standard-dose glucocorticoid group. Overall, our study indicates that PLEX improves early kidney function in patients with ANCA-associated glomerulonephritis. [Display omitted]